QUESTIONS - A FACTOR FOR GROWING CREATIVE THINKING - Babasheva Gulzavira Bektemirovna, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The article discusses the issues that affect the development of creative thinking, in particular, the pedagogical and psychological conditions and didactic requirements for the development of creative thinking in primary school students.